High-Precision GPS Tracker for Monitoring Agricultural Sprayer Drone Operations - Haryono (AI Society & STMIK Indonesia, 2025)
Efficient and precise pesticide application is critical in modern agriculture, especially when using drone technology. To ensure that spraying operations are carried out accurately in the intended locations, a reliable tracking system is essential. This newly developed Agriculture Sprayer Drone Tracker addresses this need through several key improvements over traditional methods. Previously, monitoring was performed using wired connections to check the tank, but the new system employs a wireless LoRa solution housed in a robust IP67-rated enclosure for better durability and flexibility.The tracker features a custom-designed GPS board based on the u-blox F9P module, providing high-precision location data. The GPS antenna has been optimized for a more compact form factor, resulting in a smaller, more portable device. Data is logged directly to an SD card and can be quickly accessed via a USB connection. This method offers a significant improvement over previous systems that relied on web APIs, which were often slow and dependent on internet speed. With dedicated software, users can now efficiently retrieve and save tracker data to a PC. Overall, these advancements make the tracker more versatile, reliable, and user-friendly, enhancing the effectiveness of agricultural drone spraying operations.